A Review of the Navigation HCI Research During the 2000â??s - Vainio, Teija (International Journal of Interactive Mobile Technologies (iJIM), 2010)
Two of the common problems associated with navigation research in the field of human computer interaction (HCI) systems, are the relatively narrow view that the display is able to provide for a large information space, and the impact that a diversity of contexts has on the usersâ?? divided attention. In recent years, much research has been focused on the development of navigation presentation techniques to address the first problem, and the development of capturing the context with multimodal interaction in order to address the second challenge. However, the growing number of new terminologies and techniques that has been developed has caused considerable confusion for HCI researchers, consequently making the comparison of these techniques and the generalization of empirical results of experiments very difficult, if not impossible. This article provides a taxonomy of current navigation research, which describes clearly the navigation research on desktop and non-desktop environments; it also helps to identify research domains that afford and promote the direction of navigation research. This review reveals gaps where navigation research has identified challenges but has not yet explored them.